Assessment of the patulin contamination level in selected apple-based products available in retail in Poland - Piotr Pokrzywa; Magdalena Surma (Agricultural and Food Science, 2022)
The aim of this study was to assess the level of patulin (PAT) contamination in selected apple-based products, including food intended for infants and young children, available in retail in Poland in 2016–2020. The products examined were selected due to their availability on the market and all of them derived from conventional production. All products examined contained only apples in their composition, with no other fruit added. The obtained results were related to the provisional maximum tolerable daily intake (PMTDI) of PAT established by the Joint Food and Agriculture Organization/World Health Organization Expert Committee on Food Additives (JECFA) (WHO 1995). In addition, in selected age groups, exposure assessment resulting from the intake of this toxin in the diet, was estimated. Only 2 of the 47 examined apple products contained PAT. The determined levels of contamination were significantly lower than a maximum acceptable level specified in the provisions of the food law at the level of 50.0 μg kg-1 for apple juice. When considering the value of the average daily consumption of apple juice in Poland, the PAT daily intake from apple juice did not exceed the tolerable daily intake in any of the examined samples and amounted to a maximum of 1.6% of PMTDI. As for one portion recommended for consumption, the result obtained was also below tolerable daily intake and constituted a maximum of 38.7% of PMTDI. These findings are a particularly valuable source of information for farmers, traders and consumers, and confirm health safety of apple juice and apple-based products intended for infants and young children.